Modelling an industrial anaerobic granular reactor using a multi-scale approach. (1st December 2017) - Feldman, H.; Flores-Alsina, X.; Ramin, P.; Kjellberg, K.; Jeppsson, U.; Batstone, D.J.; Gernaey, K.V.
Abstract: The objective of this paper is to show the results of an industrial project dealing with modelling of anaerobic digesters. A multi-scale mathematical approach is developed to describe reactor hydrodynamics, granule growth/distribution and microbial competition/inhibition for substrate/space within the biofilm. The main biochemical and physico-chemical processes in the model are based on the Anaerobic Digestion Model No 1 ( A D M 1 ) extended with the fate of phosphorus ( P ), sulfur ( S ) and ethanol ( E t − O H ). Wastewater dynamic conditions are reproduced and data frequency increased using the Benchmark Simulation Model No 2 ( B S M 2 ) influent generator. All models are tested using two plant data sets corresponding to different operational periods ( # D 1, # D 2 ). Simulation results reveal that the proposed approach can satisfactorily describe the transformation of organics, nutrients and minerals, the production of methane, carbon dioxide and sulfide and the potential formation of precipitates within the bulk (average deviation between computer simulations and measurements for both # D 1, # D 2 is around 10%). Model predictions suggest a stratified structure within the granule which is the result of: 1) applied loading rates, 2) mass transfer limitations and 3) specific (bacterial) affinity for substrate. Hence, inerts ( X I ) and methanogens ( X ac ) are situated in the inner zone, and this fraction lowers as the radius increases favouring the presence of acidogens ( X su, X aa, X fa ) and acetogens ( X c 4, X pro ). Additional simulations show the effects on the overall process performance when operational (pH) and loading ( S : C O D ) conditions are modified. Lastly, the effect of intra-granular precipitation on the overall organic/inorganic distribution is assessed at: 1) different times; and, 2) reactor heights. Finally, the possibilities and opportunities offered by the proposed approach for conducting engineering optimization projects are discussed. Graphical abstract: Image 1 Highlights: A multi-scale model describing an anaerobic digestion process is constructed. The model behaviour is analysed using two different industrial (full scale) data sets. The model successfully predicts COD, N, P, S, pH and mineral behaviour. Scenario analysis shows the effect of changing the operational conditions in both bulk and biofilm.